PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KETERAMPILAN PROSES SAINS FISIKA PADA HUKUM KE NOL TERMODINAMIKA - Herman Jufri Andi; Rohmah Maghfirotur (Universitas Labuhanbatu, 2022)
The purpose of this study was to determine whether or not there was a significant effect of the application of the guided inquiry learning model on science process skills in the law to zero thermodynamics. This research is a Quasy Experimentalresearch with pretest posttest control group design. The population of this research is all students of class XI even semester of Madrasah Aliyah Al-Islamiyah 1 Sumber Batu, while the sample of this research is 2 classes, where one class is used as control class and one class is used as experimental class. Based on the results of hypothesis testing using the Independent Sample T-test in the SPSS V.25 program, the value of 4,234>2,042 and significant 0.000 < 0.05. So that it can be concluded that there is a significant effect of the application of the guided inquiry learning model on science process skills in the law to zero thermodynamics.